Active fault‐tolerant control system design with trajectory re‐planning against actuator faults and saturation: Application to a quadrotor unmanned aerial vehicle. (25th November 2013) - Chamseddine, A.; Theilliol, D.; Zhang, Y.M.; Join, C.; Rabbath, C.A.
SUMMARY During the past 30 years, various fault‐tolerant control (FTC) methods have been developed to address actuator or component faults for various systems with or without tracking control objectives. However, very few FTC strategies establish a relation between the post‐fault reference trajectory to track and the remaining resources in the system after fault occurrence. This is an open problem that is not well considered in the literature. The main contribution of this paper is in the design of a reconfigurable FTC and trajectory planning scheme with emphasis on online decision making using differential flatness. In the fault‐free case and on the basis of the available actuator resources, the reference trajectories are synthesized so as to drive the system as fast as possible to its desired setpoint without violating system constraints. In the fault case, the proposed active FTC system (AFTCS) consists in synthesizing a reconfigurable feedback control along with a modified reference trajectories once an actuator fault has been diagnosed by a fault detection and diagnosis scheme, which uses a parameter‐estimation‐based unscented Kalman filter. Benefited with the integration of trajectory re‐planning using the flatness concept and the compensation‐based reconfigurable controller, both faults and saturation in actuators can be handled effectively with the proposed AFTCS design. Advantages and limitations of the proposed AFTCS are illustrated using an experimental quadrotor unmanned aerial vehicle testbed.Copyright © 2013 John Wiley & Sons, Ltd.